TOWARDS OPTIMIZING THE USE OF LIMITED LECTURE SPACE AT ARDHI UNIVERSITY, TANZANIA - Daud, Khambi; Lucian, Charles (Journal of Techno-Social, 2018)
All over the world, the number of students enrolled at higher learning institutions have been on the increase which causes shortage of space, low utilization rates and space mismatch, but many studies have found that most higher learning institutions are not using the space optimally. This study evaluates the effectiveness level of space utilization at Ardhi University’s (ARU) undergraduate classrooms by looking at the level of use and determining how it is impacted by admission of students, conditions of facilities and services and space standards. It found that space use in most ARU’s classrooms is affected by the condition and deficiency of some facilities and services, time table re-scheduling, allocating rooms to more than one program at a time (double allocation), class representatives’ preferences for rooms, by lecturers’ preferences for rooms, allocation of rooms to specific programs, current academic situation, and lecture rooms being allocated to students exceeding their capacities.